Improved methane production from brown algae under high salinity by fed-batch acclimation. (July 2015) - Miura, Toyokazu; Kita, Akihisa; Okamura, Yoshiko; Aki, Tsunehiro; Matsumura, Yukihiko; Tajima, Takahisa; Kato, Junichi; Nakashimada, Yutaka
Highlights: Fed-batch cultivation was conducted to improve methane production from brown algae. The methane production rate and salinity increased following cultivation. The methane production rate remained high, even at the equivalent of 5% NaCl. Specific bacteria and methanogens became predominant after cultivation. Abstract: Here, a methanogenic microbial community was developed from marine sediments to have improved methane productivity from brown algae under high salinity. Fed-batch cultivation was conducted by adding dry seaweed at 1 wt% total solid (TS) based on the liquid weight of the NaCl-containing sediment per round of cultivation. The methane production rate and level of salinity increased 8-fold and 1.6-fold, respectively, at the 10th round of cultivation. Moreover, the rate of methane production remained high, even at the 10th round of cultivation, with accumulation of salts derived from 10 wt% TS of seaweed. The salinity of the 10th-round culture was equivalent to 5% NaCl. The improved methane production was attributed to enhanced acetoclastic methanogenesis because acetate became rapidly converted to methane during cultivation. The family Fusobacteriaceae and the genus Methanosaeta, the acetoclastic methanogen, predominated in bacteria and archaea, respectively, after the cultivation.